Citizen, Negative Capability, and the Poetics of Doubt and Discomfiture - Lindstrom, Eric (Romanticism on the Net)

(untitled) (Université de Montréal, 2020)
Juxtaposing two very different poets—Claudia Rankine and John Keats—this essay seeks a descriptive poetic practice that responds to our current moment in the long history of American anti-Black racial injustice while addressing the value of poetic work and public feeling in terms of discourses of public health. I reintroduce a sociolinguistic practice of discomfort into Keatsian “Negative Capability,” arguing that the outlook taken from Keats’s famous December 1817 letter risks becoming a disembodied ethic of skepticism, one based on uniformly available and distributed empathy. As it offers escape into a negatively creative mode of mobile non-identity, this space of being represents a universalized mode of social imagination that draws from, and hence requires analysis informed by, the philosophy of modern racial ontologies and ideas of Blackness. Against the ingenuously “universal” tradition of philosophical skepticism, drawn here from Descartes and Hume, I frame analysis through a fugitive alternate tradition of Black skepticism. Through reading that aims to provide both close thematic comparison and a critical allegory, the essay shares extended discussion of Rankine’s volumes Don’t Let Me Be Lonely and Citizen alongside the poetry of late Keats, focusing on miseries—not simply mysteries—of knowledge. Rankine’s two “American Lyric” works explore the possibilities not only of impersonal lyric but of a sympoetics of misery. This lost situational discomfort of Keats’s Negative Capability proves useful to feel and think with only if it keeps reference to “a poetry of and between bodies,” in the words of Anthony Reed.